2015
DOI: 10.7314/apjcp.2015.16.4.1637
|View full text |Cite
|
Sign up to set email alerts
|

H2O2Inhibits Proliferation and Mediates Suppression of Migration via DLC1/RhoA Signaling in Cancer Cells

Abstract: Background: RhoGTPase-activating proteins (RhoGAPs) regulate RhoGTPases in cells, but whether individual reactive oxygen species (ROS) regulate RhoGAPs is unknown. Our previous published papers have shown that deleted in liver cancer 1 (DLC1) inhibits cancer cell migration by its RhoGAP activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…In the present study, increased excretion of ROMO1 and ROS was not observed in blood serum in the UUO model. Furthermore, H 2 O 2 is regarded as an important element that influences cellular proliferation ( 31 ). In the present study, the expression of ROMO1 was upregulated when the HK-2 cell line was treated with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, increased excretion of ROMO1 and ROS was not observed in blood serum in the UUO model. Furthermore, H 2 O 2 is regarded as an important element that influences cellular proliferation ( 31 ). In the present study, the expression of ROMO1 was upregulated when the HK-2 cell line was treated with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The production and migration of the fibers, which are primarily composed of actin and myosin, were also suppressed by H 2 O 2 in a more aggressive breast cancer cell line (MDA‐MB‐231). These results suggest that that proliferation of breast cancer cells is modulated directly by ROS via the modulation gene that encodes for the cellular cycle and apoptosis (112). These two recent findings changed the views of ROS as a deleterious molecule and even assigned it a potential essential role in the diminution of the progression in some cancers ( Fig.…”
Section: Physiological Implications Of Rosmentioning
confidence: 98%
“…Oridonin increased intracellular ROS levels, whereas pretreatment with the ROS scavenger, N ‐acetyl‐ l ‐cysteine, dramatically abrogated RAR‐α stabilization, which indicates the positive role of ROS in oridonin‐induced RAR‐α stabilization (111). In addition, Ma et al (112) observed that ROS production (H 2 O 2 ) inhibits proliferation and induces apoptosis in MCF‐7 breast cancer cells via the modulation of cell cycle and apoptosis‐related genes, and inhibits migration by decreasing stress fibers via DLC1/RhoA signaling. The production and migration of the fibers, which are primarily composed of actin and myosin, were also suppressed by H 2 O 2 in a more aggressive breast cancer cell line (MDA‐MB‐231).…”
Section: Physiological Implications Of Rosmentioning
confidence: 99%
“…The downregulating effect of superoxide anion and hydrogen peroxide on Cav-1 was mediated through a transcription-independent mechanism that involved protein degradation via the ubiquitin-proteasome pathway [ 63 ]. In H1299, non-small lung cancer cells, 100 μ M of H 2 O 2 inhibited migration, upregulated Deleted in Liver Cancer 1 (DLC1) protein expression, and reduced the activity of RhoA [ 64 ]. Thus, H 2 O 2 may be used as an inhibitor of cancer cell proliferation, migration, and invasion if used at particular concentrations and cancer cell types.…”
Section: Paradoxical Effects Of H 2 O mentioning
confidence: 99%